# Simplify the expression : 7(9k + 8) + 3 ( k-10)

justaguide | Certified Educator

To simplify 7(9k + 8) + 3 ( k-10) we first open the brackets.

Therefore 7(9k + 8) + 3 ( k-10)

= 7*9k + 7*8 + 3*k – 3*10

= 63k + 56 + 3k -30

=> 63k + 3k + 56 – 30

=> 66k + 26

Therefore 7(9k + 8) + 3 ( k-10) is equal to 66k + 26

hala718 | Certified Educator

Let E =7(9k+8) + 3(k-10)

First we will expand the brackets:

we will distribute 7:

==> E = 7*9k + 7*8 + 3*k + 3*-10

= 63k + 56 + 3k - 30

Now will group similar terms:

==> E = 63k + 3k + 56 - 30

= 66k + 26

Then E = 66k + 26

nisarg | Student

7(9k + 8) + 3 ( k-10) first multiply the contents of the parenthesis with the outside number

66k+56-30                  subtract 30 from 56

jess1999 | Student

7 ( 9k + 8 ) + 3 ( k - 10 )

First distribute

By distributing your equation should look like

63k + 56 + 3k - 30 now combine all the like terms ( 63k with 3k and 56 with -30 )

By combining, your equation should look like

atyourservice | Student

7(9k + 8) + 3 ( k-10)

multiply the number inside the parentheses by the numbers outside.

`7 xx 9k= 63k `

`7 xx 8 = 56 `

`3 xx k = 3k `

`3 xx -10= -30 `

combine like terms

`63k + 3k + 56 - 30 `

66k - 26